2017
DOI: 10.5455/jtomc.2017.10.128
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between peritoneal permeability with inflammation and subclinical atherosclerosis in peritoneal dialysis patients

Abstract: Aim: High permeability in peritoneal dialysis (PD) is reported to be associated with increased mortality. Cardiovascular disease is the most important cause of morbidity and mortality in patients with end-stage renal disease. The inflammation is thought to take part in development of atherosclerosis. The aim of this study is to investigate the relation of peritoneal permeability type with carotid intima media thickness (CIMT) in PD patients. Material and Methods: Based on the standard peritoneal equilibration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The Cancer Antigen 125 (CA-125) in serum is traditionally known as a tumor marker in ovarian cancer. Because it is also produced by the mesothelial cells of the peritoneum and is unable to overcome the pores of the peritoneal membrane due to its high molecular weight (>200 kD), CA-125 has been proposed as an alternative for assessing the integrity of peritoneal membrane 8 , 9 . A cohort study developed by Otoni et al (2000) 10 , with 15 patients at the beginning of PD, showed a significant reduction in the levels of CA-125 in the dialysate after about 60 days of follow-up (22.0 U/mL ± 4.5 vs 4.8 U/mL ± 1.3).…”
Section: Introductionmentioning
confidence: 99%
“…The Cancer Antigen 125 (CA-125) in serum is traditionally known as a tumor marker in ovarian cancer. Because it is also produced by the mesothelial cells of the peritoneum and is unable to overcome the pores of the peritoneal membrane due to its high molecular weight (>200 kD), CA-125 has been proposed as an alternative for assessing the integrity of peritoneal membrane 8 , 9 . A cohort study developed by Otoni et al (2000) 10 , with 15 patients at the beginning of PD, showed a significant reduction in the levels of CA-125 in the dialysate after about 60 days of follow-up (22.0 U/mL ± 4.5 vs 4.8 U/mL ± 1.3).…”
Section: Introductionmentioning
confidence: 99%